Analysis of trade relations between Turkey and the countries of the Organisation of Turkic States (Economics and region, 2024)
In today's world, countries often face crises. The last major crisis the world faced was the COVID-19 epidemic that occurred after the 2008 financial crisis. Avoiding crises is very difficult for any country. Many countries are trying to strengthen regional or international cooperation. Turkey has recognised the independence of the Central Asian Turkish states and Azerbaijan since 1991. Diplomatic relations between these countries were established in 1992, with mutual respect and cooperation coming to the fore. In the early 1990s, the Turkish-speaking countries sought to integrate the region, but faced various difficulties in achieving this goal. In order to strengthen its trade with other Turkish-speaking countries, Turkey has signed various agreements, such as the Free Trade Agreement (FTA) with Azerbaijan, which contribute to the growth of its economy and the welfare of its people. The Organisation of Turkic States is an excellent example of regional cooperation, and Turkey has always sought to strengthen bilateral relations with the Central Asian Turkic states and Azerbaijan. While economic relations between Turkey and the Turkic-speaking countries did not meet expectations in the last century, these countries developed bilateral economic relations in the early 2000s. This article aims to examine how economic relations between the countries of the organisation have developed with the establishment of the Organisation of Turkic States in 2021. Among the goods imported by Turkey from Central Asia in 2022, agricultural products and energy raw materials will account for the largest volume. Among the goods exported from Turkey to Turkish-speaking countries, the largest volumes are metered pharmaceuticals, textiles, and machinery. Among Turkish states, Turkey's largest trading partners are Azerbaijan and Kazakhstan. Turkey's trade with Azerbaijan and Kazakhstan did not decline in 2020, when COVID-19 spread.
Keywords: Turkey; Organisation of Turkic States; foreign trade; cooperation; Central Asia